2005
DOI: 10.1016/j.jnucmat.2005.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation kinetics of ZrNbO in steam: Differences between the pre- and post-transition stages

Abstract: Zirconium based alloys (and particularly Zircaloy-4) are widely used as cladding material of fuel rods in water-cooled nuclear reactors. However, advanced alloys are now used for longer operation time in more severe conditions. One of these new alloys is a ZrNbO, which contains 1% of Nb as alloying element (instead of Sn in the case of Zircaloy-4).This ZrNbO alloy, like many zirconium alloys, undergoes a kinetic transition, which is a sharp increase in the oxidation rate when the oxide thickness exceeds a crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…It seems that no rate-limiting step can be assumed for steam oxidation in the post-transition regime and the authors suggest that the diffusing species in the porous outer layer (surface hydroxyl groups OH Å O ) are different from those in the dense layer (oxygen ions O x O ). The conclusions are quite different with the ZrNbO alloy [21]. The assumption of a rate-limiting step can be made in the post-transition stage with an interface step as the probable rate-controlling step but neither the location (i.e.…”
Section: Post-transition Regimementioning
confidence: 78%
“…It seems that no rate-limiting step can be assumed for steam oxidation in the post-transition regime and the authors suggest that the diffusing species in the porous outer layer (surface hydroxyl groups OH Å O ) are different from those in the dense layer (oxygen ions O x O ). The conclusions are quite different with the ZrNbO alloy [21]. The assumption of a rate-limiting step can be made in the post-transition stage with an interface step as the probable rate-controlling step but neither the location (i.e.…”
Section: Post-transition Regimementioning
confidence: 78%
“…First of all, we have to remember elements from the literature date that we have to take into account for the description of the corrosion mechanism [15,34]. Especially, it has been reported that the intermetallic precipitates such as Zr(Fe, Cr) 2 play a role in the hydrogen pick-up process [35].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this particular case, isotopic labelling makes it possible to confirm that the rate-limiting steps for the kinetics of formation of the oxide are different before and after the kinetic transition. Actually, it was demonstrated in previous publications that the kinetic mechanism is completely different between the pre and post-transition regimes for as-received Zy-4 or ZrNbO samples oxidized between 500 and 550°C in steam [27,28] and for as-received Zy-4 samples oxidized at 850°C in dry air [11]. In the post-transition regime, a significant influence of steam partial pressure (when Zy-4 or ZrNbO samples are oxidized in steam) or oxygen partial pressure (when Zy-4 samples are oxidized in dry air) has been found, contrarily to the kinetic behavior before the transition.…”
mentioning
confidence: 99%